Features of vibration dampers application in the design of vibration-resistant metal cutting tools - Novitskyi, Yurii; Novitskyi, Maksym; Lytvyniak, Yaroslav (Видавництво Львівської політехніки, 2024)
Dry and viscous friction is used as a damper of oscillation energy in the construction of metal-cutting tools. A mathematical model of a two-mass oscillatory scheme of the insert of an assembled milling cutter was developed and studied, one of the masses of which models the clamped part of the insert - a press connection with dry friction, and the other - the cantilever part, which is subject to self-oscillations that are possible in the process of metal cutting. The influence of dry friction in the press joint of the insert on the amplitude of resonant oscillations of the cutter and the part was analyzed. The possibility of reducing the magnitude of the cutter's self-oscillations is demonstrated by selecting the most suitable parameters for the press connection of inserts with the body of the assembled milling cutter. The influence of internal viscous friction in materials with a high level of energy damping on the amplitude of self-oscillations of the cutter was evaluated and the possibility of their use in the design of a vibration-resistant metal-cutting tool was considered.
Keywords: self-oscillation; damping of vibration energy; structural damping; vibration amplitude; surface quality